STRATEGI KOMUNIKASI GURU DALAM MENDUKUNG PROSES PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS DI PKBM DISABILITAS PLUS TEMANGGUNG - Dahlia; Laili Syarifah; Muhammad Adam Naufal Al Ghifari (Irfani, 2025)
This study aims to analyze teachers’ communication strategies in supporting the learning process of children with special needs at PKBM Disabilitas Plus Temanggung. This institution serves as a non-formal educational center that provides inclusive learning opportunities for children with various conditions such as autism, ADHD, and intellectual disabilities. The research employs a qualitative case study method through interviews, observations, and documentation involving teachers, parents, the head of PKBM, and volunteers. Data analysis follows the Miles & Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that teachers’ communication strategies reflect Schramm’s two-way communication model, emphasizing encoding, decoding, field of experience, feedback, and shared meaning. Teachers construct adaptive learning messages using simple language, repetition, and both verbal and nonverbal channels suited to each child’s characteristics. Empathy and patience in teachers’ approaches create shared experiences that strengthen children’s understanding. Feedback from children’s expressions and behaviors serves as a basis for teachers to continuously adjust their teaching strategies. Furthermore, communication with parents reinforces the continuity of meaning between school and home. Thus, teachers’ communication strategies play a vital role in fostering inclusive learning that is adaptive, empathetic, and collaborative, ultimately supporting the independence of children with special needs in non-formal education settings.